Outcomes after gamma knife radiosurgery for intraventricular meningiomas (2022)
Background Intraventricular meningiomas (IVMs) are rare tumors with considerable treatment-associated morbidity due to their challenging location. Treatment with stereotactic radiosurgery (SRS) is sparsely reported in the literature. We describe our experience over the last 35 years using Gamma knife radiosurgery (GKRS) for IVMs. Methods We retrospectively reviewed the GKRS database identifying 2501 meningiomas treated at the University of Pittsburgh Medical Center over the last 35 years. Nineteen patients with (12 males, mean age = 53.2 years, range 14–84) 20 IVMs were identified. Headache was the most frequent presenting symptom (N = 12), and the trigone of the lateral ventricle was the most common location (N = 18). The median tumor volume was 4.8 cc (range, 0.8–17). The median margin dose was 14 Gy (range, 12–25) delivered at 50% isodose line. Results At a median follow-up of 63.1 months (range, 6–322.4) symptom control was achieved in 18 (94.7%) patients. The overall progression-free survival (PFS) was 95% at 5 years, and 85% at 10-years. After Log-rank test, patients who underwent GKRS within 12 months after diagnosis (vs. ≥ 12 months, X2: 4.455, p = 0.035), patients treated with primary GKRS without prior biopsy (vs. prior biopsy, X2: 4.000, p = 0.046), and patients with WHO grade I meningioma (vs. WHO II, X2: 9.000, p = 0.003) had a longer PFS. Imaging showed peritumoral edema in seven cases at a median of 10.5 (range, 6.13–24.3) months after GKRS. Only three of these patients were symptomatic and were successfully managed with oral medications. Cox´s regression revealed that a V12Gy ≥ 10 cc [HR: 10.09 (95% CI: 2.11–48.21), p = 0.004], and tumor volume ≥ 8 cc [HR: 5.87 (95% CI: 1.28–26.97), p = 0.023] were associated with a higher risk of peritumoral edema. Conclusion GKRS is an effective and safe management option for intraventricular meningiomas. Early GKRS should be considered as a primary management modality for small and medium sized IVM and adjuvant management for residual IVMs.